Evaluation of a multidisciplinary allied health prostate cancer clinic. Issue 3 (4th September 2017) - Crowe, Helen; Pillay, Brindha; Howard, Nicholas; Crowe, Jane; Rutherford, Max; Wootten, Addie; Corcoran, Niall; Costello, Anthony
ABSTRACT: Prostate cancer is the most common male cancer, with increasingly longer survival, and many treatment options for advanced disease. Men with prostate cancer report a high level of unmet supportive care needs. To evaluate unmet needs of a small cohort of Australian men with advanced prostate cancer, and their partners, and to assess the impact of attendance at a multidisciplinary allied health clinic on meeting these needs. Fifty patients were referred to the clinic by their treating specialists. Prior to their clinic consultations patients and partners completed study questionnaires to determine their unmet needs, prostate cancer and treatment related quality of life, levels of anxiety and depression, exercise patterns and prostate cancer‐related functional status. Questionnaires were completed again 1 month post‐clinic attendance, and pre‐and post‐clinic scores were compared. Patients reported unmet needs in several domains including psychological and sexuality needs. These showed a small reduction when assessed post‐clinic. Partners also reported needs in the psychological and emotional, and information domains. Thirty‐two percent of patients reported clinical levels of distress when assessed pre‐clinic attendance, reduced to 8% reporting the same level of distress 1 month post‐clinic. The identified high levels of unmet needs and levels of distress of this group of patients and partners highlights the necessity for additional resources to assist these men. A multidisciplinary allied health care prostate clinic as described here may further assist in the comprehensive care of these men and their partners.